Impact of water management on fertilizer and tillering dynamics in rice - Khalid, Hilyah Mohd; Mahmod, Intan Filzah; Barakbah, Syed Shahar; Osman, Normaniza (Friends Science Publishers, 2018)
Tiller is an important agronomic trait for rice yield production and its development could have been affected by different water management practices as it influences nutrient availability. This paper aims to evaluate tillering development under varying water depths and different fertilizer dosages from contrasting water management i.e. flooded and aerobic rice. Results showed that tillering development was affected by water depths and the response to fertilizer treatments altered with the change in water management where increase in tillering occurred during the early stages in flooded rice and at later stage in aerobic rice. Additionally, it takes only small percentage of fertilizer increased to boost tiller development in flooded rice whereas tillering in aerobic rice requires large percentage of fertilizer increased for it to be augmented. Therefore, increasing fertilizer dosages was found as ineffective and an alternative approach is needed to boost tiller development in aerobic rice.